Effect of edible bird’s nest extract on lipopolysaccharide-induced impairment of learning and memory in Wistar rats - Shobana, Careena; Sani, Dahiru; Tan, Sin Nee; Lim, Chee Woei; Hasan, Shariful; Mohtarrudin, Norhafizah; Kirby, Brian P.; Ideris, Aini; Stanslas, Johnson; Basri, Hamidon; Lim, Christopher Thiam Seong (Hindawi, 2018)
Cognitive disability is a common feature associated with a variety of neurological conditions including Alzheimer’s Disease (AD), Parkinson’s Disease (PD), brain injury, and stroke. Emerging evidence has demonstrated that neuroinflammation plays an important role in the development of cognitive impairment. Current available therapies are relatively ineffective in treating or preventing cognitive disabilities, thus representing an important, unfulfilled medical need. Hence, developing potential treatment is one of the major areas of research interest. Edible bird’s nests (EBN) are nests formed by swiftlet’s saliva containing sialic acid, which is believed to improve brain function. This present study was embarked upon to evaluate the learning and memory enhancing potential effect of EBN by using Morris water maze test in a Wistar rat model of LPS-induced neuroinflammation. LPS elicited cognitive impairment in the rats by significantly increasing the escape latency while decreasing the number of entries in the probe trial, which are coupled with increased production of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) and oxidative markers (ROS and TBARS) in the hippocampus. Treatment with EBN (125 mg/kg, 250 mg/kg, and 500 mg/kg; p.o.) effectively reversed the effect of LPS on escape latency and probe trial and, in addition, inhibited the LPS-induced upregulation of proinflammatory cytokines and oxidative markers. These findings are suggestive that there is existence of neuroprotective effect contained inside the edible bird’s nest.